Digital divide to virtual education: Evidence from Argentina - María José Catalán; Juan José Merlo (Atlantic Review of Economics (ARoEc), 2024)
COVID-19 forced an abrupt change in the teaching-learning process. From a scheme based on face-to-face teaching, we moved to a unique and exclusive system of virtual education. This change in the educational system involved forced adaptations of both students and teachers without a prior analysis of the required technological feasibility.This work studies the problem of digital division existing in Argentina, related to the access and use of technology and infrastructure in its educational system. From an empirical point of view, it seeks to answer the following questions: are students and teachers prepared to face a virtual learning process from a technological point of view? And what variables and factors determine technological access to the virtual education process?For this, two Virtual Education Indices are built, one aimed at students and the other at teachers, based on the access and use of PCs and mobile phones. Then, they are used to estimate a logit model for technological access for students and another for technological access for teachers.Using data from the EPH, it is analyzed how technologically prepared students and teachers are to participate in the virtual education process, at its three levels. A Technological Index of Virtual Education is built for students and another for teachers, based on the possession of a PC and the Internet and through the use of the Internet, PC and cell phone.The analysis reveals that students are better prepared from a technological point of view than teachers to be able to face the virtual education process.The most important variables that positively affect the probability of having technological access to virtual education in the case of students are: the age of the student, the total family income, the education of the student's mother, work in the labor market of the mother of the student, the number of people employed within the home and the number of inhabitants of the residential area. The negative effects on the probability of technological access to virtual education come from: attendance at public education establishments, overcrowding within the home and the number of children under 10 years of age.The probability of having technological access to virtual education in the case of teachers is positively affected by: the teacher's years of education and individual income. While the age of the teacher, overcrowding within the home and the number of inhabitants of the residential area negatively affect the probability of technological access to virtual education for teachers.
Keywords: I21; R50; O33; 330; Analysis of education; Regional analysis; Technological change